INVESTMENT MANAGEMENT LECTURE, CAPITAL MARKET TRAINING AND INVESTMENT STUDENTS INTEREST: COMBINATION OF CAPITAL MARKET THEORY AND PRACTICE - Gregorius Paulus Tahu, G. Oka Warmana, Wayan Widnyana (International Journal of Advanced Science and Technology, 2020)
The purpose of this study was to examine the effect of investment management lectures and capital market training on the interest of students investing in the capital market. This study took a sample of students from the Faculty of Economics and Business management study program at Mahasaraswati University Denpasar. The analytical tool used is multiple regression. From the test results it can be concluded that students who have taken investment management lectures have a higher interest in investing in the capital market than students who have not taken investment management lectures. Students who have participated in capital market training also show high interest in investing in the capital market.